Diphtheria in an Adult: A Paradigm of Waning Immunity - Lipika Singhal (JCDR Research and Publications Private Limited, 2021)
In the past 10 years, there have been several reported cases of the existence of a vaccine-preventable disease from several Indian states. Diphtheria, re-emerge as a major public health problem as this fatal infection used to be noticed in toddlers and school-going has now been stated to occur amongst adults also despite the fully functional Universal Immunisation Program (UIP) in India. India contributed about 53.9% of diphtheria cases globally in the year 2016. In cases, the reason for the upsurge could be attributed to lack of proper immunisation or waning of vaccine-induced immunity with increasing age. Here, a case of a 24-year-old adult male was reported who presented with acute membranous tonsillitis, a preliminary diagnosis made on physical examination. Corynaebacterium diphtheriae was isolated. Finally, the isolate was confirmed as C. diphtheriae using Matrix Assisted Laser Desorption Ionization Time of Flight Mass Spectrometry (MALDI-TOF MS) system.